HINDU INDIGENOUS HEALING: BAHARAGU CEREMONY AND ITS EFFECT ON DIARRHEA TREATMENT - I Gusti Agung Ayu Kartika; Ni Made Sinar Sari; Mida (Universitas Hindu Negeri I Gusti Bagus Sugriwa Denpasar, 2025)
Diarrhoea is a prevalent condition that may result in dehydration and severe complications if not managed. The Dayak Meratus community in Kamawakan Village, following Hindu Kaharingan customs, possesses a distinctive traditional healing technique called the Baharagu ceremony. This traditional rite combines herbal medication and spiritual purification as a comprehensive method for addressing diarrhoea and other ailments. This study seeks to delineate the execution of the Baharagu ritual, ascertain the taboos that patients are required to observe, and evaluate its effects on patient health. This study utilises a qualitative descriptive methodology through ethnographic techniques. Data collection was conducted via comprehensive interviews with balian (traditional healers), community leaders, and patients, alongside participatory observation and documentation. Data analysis was performed employing reduction, classification, and interpretation methodologies. The results demonstrate that the Baharagu ceremony comprises multiple phases, including preparation, ritual performance, and conclusion. The preparation phase entails the compilation of offerings, including ringgitan, traditional cakes, flowers, and musical instruments. Patients additionally adhere to particular dietary and behavioural limitations prior to the ritual. The essence of the ceremony transpires at night, during which the balian recites mantras, administers pelungsur (herbal medicine), and conducts a purification rite. Post-ceremony limitations, like remaining indoors and refraining from interaction with strangers, are essential for facilitating recuperation. The Baharagu ceremony has demonstrated efficacy in addressing diarrhoea among the community. This ceremony promotes social unity and strengthens traditional cultural values. This study concludes that the Baharagu ceremony is a significant cultural heritage that amalgamates conventional medicine with holistic therapy. The results provide a basis for the possible establishment of community-oriented healthcare initiatives.